The C2 domain augments Ras GTPase-activating protein catalytic activity - Maxum E. Paul; Di Chen; Kimberly J. Vish; Nathaniel L. Lartey; Elizabeth Hughes; Zachary T. Freeman; Thomas L. Saunders; Amy L. Stiegler; Philip D. King; Titus J. Boggon (Proceedings of the National Academy of Sciences, 2025)
Regulation of Ras GTPases by GTPase-activating proteins (GAPs) is essential for their normal signaling. Nine of the ten GAPs for Ras contain a C2 domain immediately proximal to their canonical GAP domain, and in RasGAP (p120GAP, p120RasGAP; RASA1 ) mutation of this domain is associated with vascular malformations in humans. Here, we show that the C2 domain of RasGAP is required for full catalytic activity toward Ras. Analyses of the RasGAP C2-GAP crystal structure, AlphaFold models, and sequence conservation reveal direct C2 domain interaction with the Ras allosteric lobe. This is achieved by an evolutionarily conserved surface centered around RasGAP residue R707, point mutation of which impairs the catalytic advantage conferred by the C2 domain in vitro. In mice, R707C mutation phenocopies the vascular and signaling defects resulting from constitutive disruption of the RASA1 gene. In SynGAP, mutation of the equivalent conserved C2 domain surface impairs catalytic activity. Our results indicate that the C2 domain is required to achieve full catalytic activity of GAPs for Ras.